The need for a systems approach to better understand the linkages between natural resources and human (im)mobility - Sonja Ayeb-Karlsson; Ilan Kelman; Gemma Hayward; Noam Levin; Kopo V. Oromeng; Caroline Zickgraf; Saleem H. Ali; Dominic Kniveton (Sustainability Science, 2026)
To date, much of the climate change literature express alarmist and groundless narratives. This includes simple linkages between natural resource loss, forced migration and violent conflict mediated through climate change, or attribution of natural resource decline to climate change, that rather relates to mismanagement, governance, and politics. There is also a mobility-bias where natural resource impacts upon immobile or ‘trapped’ people often get overlooked. More systems approach studies could widen our understanding of how the natural environment ties into people’s decisions to move or stay. In this article, we build on case study examples to propose how a systems approach can be a way forward to investigate the relationship between natural resources and human (im)mobility. We believe that the value of a systems lens is that it serves as a flexible, holistic, and effective way to identify policy interventions points and existing research gaps.

Using genomic analysis to identify tomato Tm-2 resistance-breaking mutations and their underlying evolutionary path in a new and emerging tobamovirus - Yonatan Maayan; Eswari P. J. Pandaranayaka; Dhruv Aditya Srivastava; Moshe Lapidot; Ilan Levin; Aviv Dombrovsky; Arye Harel (Archives of Virology, 2018)

Ecological bias in environmental health studies: the problem of aggregation of multiple data sources - Rakefet Shafran-Nathan; Ilan Levy; Noam Levin; David M. Broday (Air Quality, Atmosphere & Health, 2017)

ANTHOCYANIN1 from Solanum chilense is more efficient in accumulating anthocyanin metabolites than its Solanum lycopersicum counterpart in association with the ANTHOCYANIN FRUIT phenotype of tomato - Gali Schreiber; Moshe Reuveni; Dalia Evenor; Michal Oren-Shamir; Rinat Ovadia; Maya Sapir-Mir; Amir Bootbool-Man; Sahadia Nahon; Haviva Shlomo; Lea Chen; Ilan Levin (Theoretical and Applied Genetics, 2012)

Molecular dissection of Tomato leaf curl virus resistance in tomato line TY172 derived from Solanum peruvianum - Ilana Anbinder; Moshe Reuveni; Raviv Azari; Ilan Paran; Sahadia Nahon; Haviva Shlomo; Lea Chen; Moshe Lapidot; Ilan Levin (Theoretical and Applied Genetics, 2009)

Monitoring of tumor response to chemotherapy in vivo by a novel small-molecule detector of apoptosis - Hagit Grimberg; Galit Levin; Anat Shirvan; Avi Cohen; Merav Yogev-Falach; Ayelet Reshef; Ilan Ziv (Apoptosis, 2009)

Molecular imaging of cell death in vivo by a novel small molecule probe - Revital Aloya; Anat Shirvan; Hagit Grimberg; Ayelet Reshef; Galit Levin; Dvora Kidron; Avi Cohen; Ilan Ziv (Apoptosis, 2006)

Temporally extended gene expression of the ADP-Glc pyrophosphorylase large subunit (AgpL1) leads to increased enzyme activity in developing tomato fruit - Marina Petreikov; Shmuel Shen; Yelena Yeselson; Ilan Levin; Moshe Bar; Arthur A. Schaffer (Planta, 2006)

A simple plant regeneration-ability assay in a range of Lycopersicon species - Benjamin Steinitz; Anat Amitay; Victor Gaba; Yona Tabib; Menachem Keller; Ilan Levin (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

The tomato homolog of the gene encoding UV-damaged DNA binding protein 1 (DDB1) underlined as the gene that causes the high pigment-1 mutant phenotype - Michal Lieberman; Orit Segev; Nehama Gilboa; Avraham Lalazar; Ilan Levin (Theoretical and Applied Genetics, 2004)

Identification of epistatic interaction affecting glycoalkaloid content in tubers of tetraploid potato (Solanum tuberosum L.) - Jacob van Dam; Ilan Levin; Paul C. Struik; David Levy (Euphytica, 2003)

Genetic characterisation of tetraploid potato (Solanum tuberosum L.) emphasising genetic control of total glycoalkaloid content in the tubers - Jacob van Dam; Ilan Levin; Paul C. Struik; David Levy (Euphytica, 1999)